Friday, 15 June 2018 2018
DOI: 10.1136/annrheumdis-2018-eular.2296
|View full text |Cite
|
Sign up to set email alerts
|

FRI0103 One-year follow-up of a nationwide cohort of patients with inflammatory arthritis, who switched from originator to biosimilar etanercept, focusing on patients who switched back to originator. an observational danbio study

Abstract: BackgroundIn Denmark, patients (pts) treated with originator etanercept (ETA) 50 mg SC conducted a mandatory non-medical switch to biosimilar SB4 in April 2016 (switchers). Pts treated with 25 mg ETA or 50 mg powder-solution were not mandated to switch (non-switchers). Some switchers resumed ETA during follow-up (back-switchers).ObjectivesTo investigate the frequency of back-switching after the non-medical switch from ETA to SB4, and in back-switchers to study, 1) baseline characteristics at the time of initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…However, conclusions could not be drawn because the RFs identified were markers of higher disease activity and treatment failure (online supplemental material, table 1). 11–13 25–27…”
Section: Methodsmentioning
confidence: 99%
“…However, conclusions could not be drawn because the RFs identified were markers of higher disease activity and treatment failure (online supplemental material, table 1). 11–13 25–27…”
Section: Methodsmentioning
confidence: 99%
“…Notably, the least common reason for switching or discontinuing treatment was patient preference, which is in line with the finding that numerous studies included in this review state that the initial switch, in which patients cycle from originator to biosimilar products, was due to non-medical reasons and mandated by healthcare payers. 18,31,32,43,44,49,50,54,55,62,80 This is in contrast to switching to a treatment with another MoA, which generally occurs due to medical reasons 2 and is less related to mandates issued by payers. In this context, it is of interest to note that an overall originator-to-biosimilar switching strategy has been recommended by several healthcare authorities 3,85 and that this review found that the most commonly cited reason for switching back to the originator drug from biosimilar treatment was adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…It is also worth noting that the three studies by Glintborg et al all use the DANBIO registry and that the overlap of patients is therefore likely to be considerable. 18,49,50 This is especially pertinent for the two conference abstracts, both of which focus on patients treated with etanercept. However, as the population size, patient baseline characteristics, and number of treatment switches differ between the two publications, both were included as it was not possible to discern the amount of overlap.…”
Section: Discussionmentioning
confidence: 99%
“…Immuno-Rheumatology research group; 2 Immunology, University Hospital La Paz, Madrid, Spain Background: Rituximab (Rtx), a monoclonal antibody against CD20+, induces transient depletion of B cells and was approved for the treatment of patients with active rheumatoid arthritis (RA). Previous data 1 showed that Rtx is particularly effective on autoimmune diseases in which auto-antibodies (auto-Ab) are produced.…”
mentioning
confidence: 99%